Mental Simulation of Painful Situations Has an Impact on Posture and Psychophysiological Parameters - Lelard, Thierry; Godefroy, Olivier; Ahmaidi, Said; Krystkowiak, Pierre; Mouras, Harold (Frontiers in Psychology, 2017)
Embodiment is made possible through the ability to imagine ourselves in a situation (men- tal simulation). Postural changes were demonstrated in response to painful situations but the effect of an implicit instructionwas not studied. The present study intended to record the dif- ferential responses when subjects were instructed or not to imagine themselves in a painful or a non painful situation. Painful stimuli and instructions to simulate mentally the displayed situation were hypothesized to induce postural changes that could be evidenced by changes in the Centre Of Pressure (COP)’s trajectory as compared to viewing the same stimuli with- out any instruction. We hypothesized that the mental simulation of a painful situation would induce an embodiment of the emotional situation indexed by a rearward position of the COP and physiological responses as compared to the passive observation of the same visual scene. 31 subjects participated in this study and were standing quietly on a posturographic plat- form while visual stimuli depicting scenes defining three experimental conditions (painful, non-painful and neutral situations) were presented for 12s. Physiological measures (heart rate and electrodermal activity) and postural responses (COP displacements) were recorded in response to the stimuli with or without the instruction to imagine themselves within the situation. Time course analyses (1s sliding window) were conducted for several postural parameters, heart rate and electrodermal response. An interaction effect (instruction x stimuli x time) demonstrated that mental simulation induced a rearward displacement of the mean position of the COP at different time during the presentation (4s; 9-12s). An effect of instruction was reported for both Heart Rate (HR) (HR was higher in the mental simulation condition)while a stimulation effect was reported only for HR (lower for painful stimuli than for non-painful stimuli). The results of our time course analyses demonstrated the embodiment of painful situa- tions through postural control modulations and physiological changes depending on whether the participants have or not the instruction to imagine themselves in the situation.